THE ROLE OF MODERN METHODOLOGY IN LANGUAGE TEACHING (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
In recent decades, language teaching has undergone significant transformation due to advancements in educational psychology, technology, and globalization. This article explores the impact of modern methodologies on language instruction, emphasizing the shift from traditional grammar-translation methods to communicative and learner-centered approaches. It analyzes the effectiveness of task-based, content-based, and technology-enhanced teaching methods in improving learners’ communicative competence and language proficiency.